2022
DOI: 10.1073/pnas.2113629119
|View full text |Cite
|
Sign up to set email alerts
|

Climate and agronomy, not genetics, underpin recent maize yield gains in favorable environments

Abstract: Quantitative understanding of factors driving yield increases of major food crops is essential for effective prioritization of research and development. Yet previous estimates had limitations in distinguishing among contributing factors such as changing climate and new agronomic and genetic technologies. Here, we distinguished the separate contribution of these factors to yield advance using an extensive database collected from the largest irrigated maize-production domain in the world located in Nebraska (Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 49 publications
1
65
0
1
Order By: Relevance
“…Our finding of larger contribution of agronomic practice to variation in yield than genetic improvement is compatible with previous studies on rice in Japan and on maize in US ( Horie et al, 2005 , Rizzo et al, 2022 ), which showed limited contribution of genetic improvement in yield potential to yield increase in farmers’ fields. The variation in total yield gain was associated with production system, management factor, and season.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of larger contribution of agronomic practice to variation in yield than genetic improvement is compatible with previous studies on rice in Japan and on maize in US ( Horie et al, 2005 , Rizzo et al, 2022 ), which showed limited contribution of genetic improvement in yield potential to yield increase in farmers’ fields. The variation in total yield gain was associated with production system, management factor, and season.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the widespread adoption of precision-farming technologies and crop breeding improvements has supported the increase in yield. Specifically, Rizzo et al (2022) , determined that the increased yield in corn was attributed to a decadal climate trend (48%), agronomic improvements (39%), and improvement in genetic yield potential (13%). It is important to note that the continued decrease in corn water intensity for beef production has a trickledown effect that results in a lower water intensity for accompanying coproducts such as distillers-grains.…”
Section: Resultsmentioning
confidence: 99%
“…Grain filling rate is affected by both genotype and environmental conditions, and light stress responses vary by genotype (Li et al, 2005). However, Rizzo et al (2022) concluded that genetic improvement accounted for only 13% of yield increase, and that if genetic progress in yield potential was also slowing in other environments and crops, future crop-yield gains would increasingly rely on improved agronomic practices. Additionally, Li and Wang (2009) reported that breeding cultivars tolerant to high planting density and other adverse conditions would be the most effective cultivation measure for improving maize grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Grain filling in maize is influenced by various factors, for instance, genetics (Borrás et al, 2009;Li et al, 2020), irrigation methods and drought stress (Ahmad et al, 2022;Cao et al, 2022), fertilizer application (Zhang et al, 2021;Wu et al, 2022), and planting patterns and sowing densities (Jia et al, 2018). However, the amount of solar radiation received during the growing season is the most critical factor that determines the grain filling rate of maize (Shi et al, 2013(Shi et al, , 2018Chen et al, 2014;Rizzo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%